Innovate in teaching geography: report of experience in the remote model in a school in the rural area of Santana do Matos/RN - Santos, Geovar Miguel dos; Silva, Julliana Araújo da; Dantas, Bárbara de Medeiros; Garcia, Tânia Cristina Meira (Revista Ensino de Geografia (Recife), 2021)
This work is an experience report developed with the students of the 5th grade of elementary school ina rural school, in the city of Santana do Matos / RN. The pedagogical practice developed with the students revolved around the process of modernizing economic activities, means of communication and transportation, and aimed to answer the following question: how does technological advances contributeto the modernization of human activities? In order to carry out this school intervention proposal, activities were developed synchronously, using the Google Meet application and asynchronously, by the Google Classroom and WhatsApp applications, thus, this intervention was anchored in the inverted classroom methodology, in which we find its conceptual and theoretical-descriptive foundations in the writings of Jonathan Bergmann and Aaran Santos (2018), and of remote teaching, based on Garcia et. al (2020). Methodologically, a bibliographic research was carried out and the field diary and photographic records were used. With such a report, it is notable that in the context of social distance due to the pandemic that has plagued the world in the beginning of the decade, active methodologies are presented as a solution to propose pedagogical practices that aim to train students in Geography teaching from a perspective critical and reflective, in order to shorten distances and provide learning opportunities